Development of Cholesterol-Lowering and Detox Formulations Using Bentonite and Herbal Ingredients - Turgut, Rana; Kartal, Murat; Akkol, Esra Küpeli; Demirbolat, İlker; Taştan, Hakkı (Frontiers in Pharmacology, 2021)
Detoxification enzymes involved in human metabolism works to minimize the potential xenobiotic-induced damage constantly. Studies have revealed that toxin accumulation plays an important role in the etiology of cardiovascular disease. This study has been designed to provide evidence of medicinal use of bentonite, turmeric (Curcuma longa L.), grape (Vitis vinifera L.) seed, flaxseed (Linum usitatissimum L.), and psyllium (Plantago ovata L.) as detoxification and cholesterol-lowering agents using a hypercholesterolemic model in mice. The potential hypocholesterolemic effects and detoxification ability of these ingredients were evaluated at the same time: Total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglyceride, glucose, aspartate aminotransferase, alanine aminotransferase, malondialdehyde, plasma total antioxidant activity, nitric acid, leptin levels and glutathione, glutathione peroxidase, lipid peroxidation, superoxide dismutase and catalase values were measured. It was determined that GBTF group (grape seed extract, bentonite, turmeric, and flaxseed), GBTP group (grape seed extract, bentonite, turmeric, and psyllium), and GBT group (grape seed extract, bentonite, and turmeric) of the tested materials decreased the serum total cholesterol concentration by 64.8%, 57.5%, and 48.9%, respectively, in mice fed a high cholesterol diet. In addition, it was determined that some detoxification parameters such as superoxide dismutase, catalase, glutathione, and glutathione peroxidase were statistically significantly reversed in GBTF, GBTP, and GBT groups. Flaxseed, psyllium, and bentonite clay did not show significant effects in reducing total cholesterol; however, GBTF, GBTP, and GBT groups interventions had a significant effect in reducing total cholesterol levels. Moreover, it was observed that adding flaxseed or psyllium to the GBT group increased the cholesterol-lowering effect. Therefore, it can be thought that this significant effect is due to the synergistic effect of the raw materials. When the results obtained were evaluated, it was seen that the cholesterol-lowering and detoxification effects of the combinations were higher than from the effect of natural material used alone. As a result, combinations of some of these ingredients have a positive effect on reducing the risk of cardiovascular disease.